Potential application of Ganoderma lucidum in solid state fermentation of primary sludge and wheat straw - Jesus, João Paulo Furlan de [UNESP]; Sain, Mohini; Jeng, Robert; Negrão, Djanira Rodrigues; Leão, Alcides Lopes [UNESP]; Andrade, Meire Cristina Nogueira de; Minhoni, Marli Teixeira de Almeida [UNESP] (North Carolina State Univ Dept Wood &paper Sci, 2015)
This study was conducted to investigate the production of lignocellulolytic enzymes and sugars by the fungus Ganoderma lucidum during solid state fermentation (SSF) using primary sludge (PS) and wheat straw (WS) as substrates at different concentration ratios. For fungal growth on SSF, 20 g of each blended substrate was added to Erlenmeyer flasks, which were autoclaved and maintained at room temperature prior to inoculation, whereas for submerged fermentation (SF), flasks containing 25 mL of potato dextrose broth (PDB) were used as standard to check the differences between both methods of growth, and then all flasks were incubated at 25 degrees C in the dark, during 8 and 16 days. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis from the protein extract obtained from solid state fermentation strongly suggested that G. lucidum could produce lignocellulolytic enzymes to degrade primary sludge and wheat straw. Among the sugars, the production of xylose and mannose was disturbed by adding primary sludge. With the addition of primary sludge, high glucuronic acid content was observed. The results suggest that the combination of primary sludge and wheat straw, at concentration ratios of 1: 1 to 1: 3, respectively, can be used as a raw material in the production of lignocellulolytic enzymes and the bioconversion of other types of biomass by G. lucidum.
Keywords: Ganoderma lucidum; Solid state fermentation; Lignocellulolytic enzymes